TLC Bioautography Analysis of Sappan (Caesalpinia sappan L.) Wood Extract Against Propionibacterium acnes and Staphylococcus epidermidis Bacteria - Aisya, A. Henni; Naid, Tadjuddin; Amin, Asni; Kalsum T, Ummu; Ramlan, Pratiwi (Jurnal Fitofarmaka Indonesia, 2023)
Sappan wood (Caesalpinia sappan L.) is one of the plants that is widely used in traditional medicine in Indonesia. Sappan wood is known to have several benefits, including its ability to treat several infectious diseases caused by bacteria. The aim of this research is to determine the class of active compounds that have antibacterial activity against Propionibacterium acnes and Staphylococcus epidermidis using TLC Bioautography analysis. The TLC results showed that the ethanol extract of Sappan wood contains alkaloid, flavonoid and phenol compounds. Bioautography TLC results show that the ethanol extract of Sappan wood has the potential for good antibacterial activity against the bacteria Propionibacterium acnes and Staphylococcus epidermidis with Rf values of 1: 0.92, Rf 2: 0.78, Rf 3: 0.65, Rf 4: 0.50, Rf 5: 0.38, Rf 6: 0.23 and Rf 7: 0.09 for Propinibacterium acnes. And the values of Rf 1: 0.65, Rf 2: 0.50, Rf 3: 0.38, Rf 4: 0.23 and Rf 5: 0.09 for Staphylococcus epidermidis.